Impacts of Macro Economic Variables on the RMG Export Growth of Bangladesh - Shimu Afroza Ahammed; Islam Md. Shahidul (Economics and Business)
The ready-made garments (RMG) sector of Bangladesh is considered as a key driver for the Bangladeshi Economy. This paper tries to examine the impacts of macroeconomic variables on the RMG export growth of this country. For this purpose, secondary data was collected from various sources. Multiple linear regression model was applied to measure the effects of macroeconomic variables on the RMG export growth. Trade Entropy and the Competitiveness Index were applied to understand the status of RMG sector in the world market. After that, to check the accuracy of the regression model, three types of econometric problems were tested in this study. Firstly, heteroscedasticity problem was tested by graphical presentation. Secondly, auto-correlation problem was tested by Durbin Watson test. Thirdly, multicollinearity problem was tested by correlation matrix and Variance Influence Factor (VIF). The empirical results show that for every unit increase of the growth rate of official exchange rate, inflation rate, real interest rate, and female unemployment rate; the growth rate of RMG export decreases by 1.159, 0.055, 0.034, and 0.068 units, respectively.